Experimental use of electronic nose for odour detection. (2015) - Sharma, Vishal; Panchariya, P.C.
An electronic nose is an intelligent system for discrimination of odours and used to mimic the human nose of smell. Tin oxide semiconductor gas sensors are used for the development of electronic nose. It employs an array of chemical gas sensors, a sample handling system and a pattern recognition system. These techniques allow the system for a high degree of selectivity and reversibility. The ideal gas sensor has properties like reversibility, selectivity, robustness, sensitivity and reliability. After signal processing and feature extraction, a unique 'smell print' of the substance is obtained for classification, concentration measurement and to judge the quality. This paper describes the function of electronic nose, its applications and detecting the smell of particular volatile organic compound like benzene, acetone and ethanol at different concentrations. The obtained characteristics and response from electronic nose indicates that it can be used for distinct applications like pharmaceutics, defence and security industries.